Anxiety Of Tim Thomas Guilty Feelings In Seven Pounds Movie Directed By Gabrielle Muccino: A Psychoanalytic Approach - Altesar, Kukuh Iman, Drs. Abdillah Nugroho, M. Hum, Titis Setyabudi, S.S., M.Hum (2013)
The problem of the study is to reveal how is major character reflects his anxiety. The objective of the study is to analyze the film based on its structural analysis and based on the psychoanalytic analysis. This study is qualitative study. The object of the study is Seven Pounds movie directed by Gabrielle Muccino and written by Grant Nieporte published in 2008 in New York by Columbia Picture. The data sources are divided into two namely primary data source and secondary data source. The primary data source is the film itself and the secondary data source is the other sources related to the analysis such as references, author's biography, criticisms relation to the problems and material related to the study whether picking up from books or internet. The methods of data collection are observation and library research. The technique of data analysis is descriptive analysis. Based on the analysis, the writer concludes that the problems of the major character cause the conflict of his mental condition. It happens when there is contradiction between Id, Ego, and Superego and it brings him into anxiety.